2021
DOI: 10.1186/s13677-021-00231-z
|View full text |Cite
|
Sign up to set email alerts
|

Container orchestration on HPC systems through Kubernetes

Abstract: Containerisation demonstrates its efficiency in application deployment in Cloud Computing. Containers can encapsulate complex programs with their dependencies in isolated environments making applications more portable, hence are being adopted in High Performance Computing (HPC) clusters. Singularity, initially designed for HPC systems, has become their de facto standard container runtime. Nevertheless, conventional HPC workload managers lack micro-service support and deeply-integrated container management, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 34 publications
0
7
0
2
Order By: Relevance
“…Furthermore, it removes the complexity of having to set up VMs and application runtimes by packaging the applications and runtimes as containers. This last point has been confirmed by Zhou et al [12], who investigated using Kubernetes and containers for HPC and found that it significantly improved portability and eased the installation of dependencies.…”
Section: Related Workmentioning
confidence: 57%
“…Furthermore, it removes the complexity of having to set up VMs and application runtimes by packaging the applications and runtimes as containers. This last point has been confirmed by Zhou et al [12], who investigated using Kubernetes and containers for HPC and found that it significantly improved portability and eased the installation of dependencies.…”
Section: Related Workmentioning
confidence: 57%
“…As a result, it can meet the needs of cloud-based industries. Kubernetes is also suitable for data-intensive jobs in cloud clusters and shows better performance for HPC clusters [153]. Furthermore, Kubernetes promotes innovation and advantages in future IoT and edge hardware.…”
Section: Kubernetes Was Initially Designed and Developed Bymentioning
confidence: 99%
“…The most recent research in this area [16] proposes a hybrid architecture of Kubernetes with Terascale Open-source Resource and QUEue Manager (TORQUE) for running and orchestration virtual HPC clusters over Kubernetes using usually the well-known Portable Batch System (PBS) notation. The proposed approach benefits from adding the TORQUE operator into the Kubernetes and utilizing both technologies, although, this adds significant complexity to the deployment.…”
Section: Related Workmentioning
confidence: 99%